2009
DOI: 10.1111/j.1399-6576.2009.02035.x
|View full text |Cite
|
Sign up to set email alerts
|

Does 1 or 2 g paracetamol added to ketoprofen enhance analgesia in adult tonsillectomy patients?

Abstract: Combining paracetamol i.v. with ketoprofen at the end of tonsillectomy did not reduce the proportion of the patients requiring rescue analgesia, but the number of opioid doses was less in the add-on groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 25 publications
(22 reference statements)
1
22
0
1
Order By: Relevance
“…Five randomized, placebo-controlled trials were identified; all compared intravenous acetaminophen with placebo. [31][32][33][34][35] The benefit of intravenous acetaminophen over its comparator in pain control and opioid consumption was not consistent across the studies. None of the studies found a significant difference in the rate of postoperative nausea and vomiting between treatment groups.…”
Section: Otolaryngologic Surgerymentioning
confidence: 98%
See 1 more Smart Citation
“…Five randomized, placebo-controlled trials were identified; all compared intravenous acetaminophen with placebo. [31][32][33][34][35] The benefit of intravenous acetaminophen over its comparator in pain control and opioid consumption was not consistent across the studies. None of the studies found a significant difference in the rate of postoperative nausea and vomiting between treatment groups.…”
Section: Otolaryngologic Surgerymentioning
confidence: 98%
“…Five randomized, placebo‐controlled trials were identified; all compared intravenous acetaminophen with placebo . The benefit of intravenous acetaminophen over its comparator in pain control and opioid consumption was not consistent across the studies.…”
Section: Clinical Trialsmentioning
confidence: 99%
“…At the same time, a national survey distributed across England, Wales, Scotland and Northern Ireland declared paracetamol, nonsteroidal anti-inflammatory drugs (NSAID's), strong opiates and antiemetics as the main analgesic modalities used after tonsillectomy surgery in children [1]. Intravenous paracetamol has been demonstrated to decrease the needed opioid doses after adenotonsillectomy when it has been combined with ketoprofen and administered intravenously at the end of the operation [14].…”
Section: Discussionmentioning
confidence: 99%
“…In 114 tonsillectomy patients (ranging in age from 16 to 50 years), adding 1 or 2 g of IV acetaminophen to IV ketoprofen 1 mg/kg did not significantly reduce pain compared to ketoprofen alone, but acetaminophen patients consumed less rescue analgesia (27% less in the 1 g acetaminophen group, P = 0.023 and 38% less in the 2 g group, P = −0.002) 92 …”
Section: Opioid‐sparing Effects Of Acetaminophen Combination Therapymentioning
confidence: 97%
“…In 114 tonsillectomy patients (ranging in age from 16 to 50 years), adding 1 or 2 g of IV acetaminophen to IV ketoprofen 1 mg/kg did not significantly reduce pain compared to ketoprofen alone, but acetaminophen patients consumed less rescue analgesia (27% less in the 1 g acetaminophen group, P = 0.023 and 38% less in the 2 g group, P = )0.002). 92 A randomized study of 87 patients undergoing elective breast surgery divided patients to receive 1 g IV acetaminophen or 1 g IV metamizol or placebo, all delivered 20 minutes before surgery and then 4, 10, and 16 hours after tend of the procedure. 93 No significant differences among groups was noted in rescue morphine consumption, but more IV acetaminophen patients did not receive any rescue medication compared to placebo patients (42% vs. 4%, respectively).…”
Section: Acetaminophen (Iv Paracetamol)mentioning
confidence: 99%